POLICY ANALYSIS OF ISLAMIC EDUCATION MANAGEMENT PROGRAM CURRICULUM DEVELOPMENT IN PREPARING QUALITY GRADUATES IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - St Rodliyah (Fenomena, 2022)
Artikel ini bertujuan untuk mengetahui hasil analisi kebijakan pengebangan kurikulum prodi MPI S1 FTIK IAIN Jember dalam menyiapkan lulusan bermutu pada era revolusi industry 4.0. Kurikulum memegang kedudukan kunci dalam pendidikan, sebab berkaitan dengan penentuan arah, isi dan proses pendidikan, yang pada akhirnya menentukan mutu lulusan suatu lembaga pendidikan. Mutu pendidikan menjadi harapan bagi semua pihak yang terlibat dalam dunia pendidikan. Setidaknya ada 2 hal yang menjadi alasan  mengapa mutu pendidikan itu menjadi penting bagi masyarakat. Pertama, aspek persaingan. Persaingan terjadi baik antar lembaga pendidikan  maupun dalam dunia kerja. Pada Era Industri 4.0 calon tenaga kerja harus dibekali dengan  pendidikan yang bermutu dan keterampilan menggunakan Informasi Teknologi (IT)  untuk mendapatkan pekerjaan yang lebih baik. Kedua, munculnya kebebasan dan otonomi bagi institusi pendidikan yang mengharuskan pentingnya mutu di setiap jenis, jalur, dan jenjang pendidikan. Semua orang berkepentingan dengan kurikulum khususnya para pengelola pendidikan, sebab kita sebagai orang tua, sebagai  warga masyarakat, sebagai pemimpin formal ataupun informal selalu mengharapkan tumbuh dan berkembang peserta didik, pemuda, dan generasi muda yang lebih baik, lebih cerdas, berkemampuan tinggi, dan sukses. Kurikulum memiliki andil yang cukup besar dalam melahirkan harapan tersebut. Untuk itu kurikulum harus selalu di evaluasi setiap tahun hasilnya digunakan sebagai analisis kebijakan pengembangan kurikulum yang sesuai dengan perubahan zaman, pengembangan IPTEK,  tuntutan kebutuhan peserta didik, dan tuntutan kebutuhan masyarakat sebagai pengguna lulusan. This article aims to determine the results of policy analysis of the curriculum development of the Islamic Education Management Program (MPI), Faculty of Tarbiyah and Educational Sciences (FTIK), UIN Kiai Haji Achmad Siddiq Jember in preparing quality graduates in the Industrial Revolution 4.0. The curriculum holds a key position in education because it is related to the direction, content, and educational process, which ultimately determines the quality of graduates of an educational institution. The quality of education is hope for all parties involved in education. There are at least 2 reasons why the quality of education is essential for the community. First is the competitive aspect. Competition occurs both between educational institutions and in the world of work. In the era of industry 4.0, prospective workers must be provided with quality education and skills to use information technology (IT) to get a better job. Second, the emergence of freedom and autonomy for educational institutions requires the importance of quality in every type, path, and level of education. Everyone is interested in the curriculum, especially the managers of education, because we as parents, as citizens, as formal or informal leaders always expect to grow and develop students, youth, and the younger generation are better, more intelligent, highly capable, and successful. The curriculum has a considerable share in the birth of these expectations. For this reason, the curriculum must always be evaluated every year; the results are used as an analysis of the development policy of the curriculum by the changing times, the development of science and technology, the demands of the needs of students, and the demands of the needs of the community as a graduate user.